ANALISIS ISI PESAN DAKWAH PADA MEDIA SOSIAL DALAM AKUN INSTAGRAM RUMAYSHOCOM - Ahmad Amien Imrafit; Nunu Burhanuddin (KOLONI, 2023)
The development of technology at this time is very rapid, one of the media that can be utilized to convey da'wah is Instagram. The @rumayshocom account is one of the accounts engaged in da'wah by posting da'wah through pictures and videos and given Hadith and Al-Qur'an quotes in the post. This is an opportunity for da'wah in conveying the teachings of Islam. This study aims to determine the content of da'wah messages contained in the @rumayshocom account during the May 2022 period. This research uses a qualitative approach with a type of library research. The analysis process in this study goes through two stages, namely by analyzing the da'wah message from the message of faith, sharia and morals. The data analysis technique uses Philipp Mayring's content analysis. The results of this study indicate that da'wah messages through Instagram in the categories of creed, sharia and morals contain invitations to do good and always warn about the problems of the world and the hereafter. The content of the da'wah message is in accordance with the indicators of each content of the da'wah message such as the virtues of keeping ablution, socializing, being devoted to your husband and respecting time. Keywords: Content analysis of da'wah messages, Social media, @rumayshocom